Las condiciones políticas que limitan a los jóvenes sus alternativas de participación social ciudadana en el centro poblado rural de ciudad de dios, distrito de laredo, en el año 2014 - Panta Farfan, Soila Amarilis (2015)
In the present research report there developed the study relating to the political conditions of the Populated Rural Center of God's City, characterized by the crisis of values and the negative attitude of the official institutions they propitiate limited modals of alternatives of social civil participation in the young population between the ages from 18 to 24 years. The crisis of values of the official institutions, they disorient the formative process of the young population between the ages from 18 to 24 years of the Populated Rural Center of God's City, for which they carry to limiting his civil participation. The negative attitude of the official institutions, they contribute in order that the young population between the ages from 18 to 24 years of the Populated Rural Center of God's City, they do not have definite modals of social civil participation. The discredit and deslegitimación of the traditional representations of participation of the political parties it owes to his aged doctrinaire slogans, for which, these mechanisms of caducity of the old political class do that them and the young women between the ages from 18 to 24 years of the people of God's City reflect the diffuse one and the absence of interpretation and permanent participation of the political culture and of not valuation and comprehension in the public life